Use of customized healing abutment in immediate implantation of tooth 36 for peri-implant tissue preservation: A case report (Research, Society and Development, 2025)
The creation of a customized healing cap, an implant component that aids in healing and adequate contouring of soft tissues, can be done using fluid resin. This procedure aims to preserve the original contour of peri-implant tissues and simplify the steps by not requiring a second surgical procedure, in addition to enabling more predictable results with its use. The objective of this study was to report a clinical case of extraction of the first permanent lower left molar (tooth 36) due to root fracture, with immediate implant installation and creation of a customized healing cap, aiming to highlight the benefits of using this type of healing cap for peri-implant tissue preservation, in addition to showing the importance of CBCT for the diagnosis of root fracture. The results proved that the use of the customized healing cap contributed significantly to the maintenance of soft and hard tissues, minimizing bone resorption and promoting better aesthetics and functionality of oral rehabilitation. The importance of CBCT in aiding the diagnosis of root fractures was demonstrated. It is concluded that this approach represents a viable alternative to optimize results in immediate implants, suggesting further research to deepen its applicability in different clinical contexts.